A qualitative metasynthesis exploring the impact of prostate cancer and its management on younger, unpartnered and gay men. (5th April 2017) - Matheson, L.; Watson, E.K.; Nayoan, J.; Wagland, R.; Glaser, A.; Gavin, A.; Wright, P.; Rivas, C.
Abstract : Prostate cancer (PCa) can negatively impact on men's sexual, urinary and emotional functioning, affecting quality of life. Most men with PCa are older (≥65 years), married and heterosexual and little is known about the impact on men who are younger, unpartnered or gay. We aimed to synthesise existing qualitative research on these three groups of men. A systematic metasynthesis was undertaken that included data on the unique impacts of PCa on younger (<65 years) ( n  = 7 papers), unpartnered ( n  = 17 papers) or gay or bisexual men ( n  = 11 papers) using a modified meta‐ethnographic approach. The three overarching constructs illustrated the magnified disruption to men's biographies, that included: marginalisation, isolation and stigma —relating to men's sense of being "out of sync"; the burden of emotional and embodied vulnerabilities and the assault on identity —illustrating the multiple threats to men's work, sexual and social identities; shifting into different communities of practice— such as the shift from being part of a sexually active community to celibacy. These findings suggest that PCa can have a particular impact on the quality of life of younger, unpartnered and gay men. This has implications for the provision of tailored support and information to these potentially marginalised groups.